2018
DOI: 10.1111/1755-5922.12457
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of nonvitamin K antagonist oral anticoagulants during catheter ablation of atrial fibrillation: A systematic review and meta‐analysis

Abstract: Use of NOACs compared to VKAs significantly reduced the risk of bleeding in patients with AF ablation. Similarly, the risk of bleeding was lower with uninterrupted NOACs than with uninterrupted VKAs, and with interrupted NOACs than with interrupted VKAs. The rate of thromboembolic complications was extremely low in both study groups without any differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A meta-analysis by Wu et al found comparable efficacy and safety of DOACs to warfarin in 11,686 patients undergoing catheter ablation for atrial fibrillation, albeit the risk for minor bleeding was lower with DOACs than warfarin [21]. The DOAC associated reduced risk of bleeding during catheter ablation for atrial fibrillation was also confirmed by Ge et al in a systematic review and meta-analysis involving 12,644 patients [22]. Among DOACs, dabigatran, the first available DOAC, was the least prescribed DOAC.…”
Section: Discussionmentioning
confidence: 81%
“…A meta-analysis by Wu et al found comparable efficacy and safety of DOACs to warfarin in 11,686 patients undergoing catheter ablation for atrial fibrillation, albeit the risk for minor bleeding was lower with DOACs than warfarin [21]. The DOAC associated reduced risk of bleeding during catheter ablation for atrial fibrillation was also confirmed by Ge et al in a systematic review and meta-analysis involving 12,644 patients [22]. Among DOACs, dabigatran, the first available DOAC, was the least prescribed DOAC.…”
Section: Discussionmentioning
confidence: 81%
“…In the clinical scenarios of catheter ablation and cardioversion procedures, the guidelines reviewed shared similar approaches regarding the use of OAC and NOACs. Several studies have examined the use of uninterrupted NOACs in the catheter ablation setting and all data support better safety profile compared to VKAs, with no differences in terms of efficacy 54,55 . In the cardioversion setting NOACs were similar to VKAs in terms of both efficacy and safety 56 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In four open-label controlled trials investigating the best OAC strategy in subjects undergoing left atrial catheter ablation of AF, the rates of bleeding were lower or comparable with uninterrupted NOACs than with uninterrupted warfarin with target INR 2.0-3.0 [31][32][33][34]. The safety of NOACs in this setting has also been demonstrated in reallife patients [35,36]. Thus, NOACs are a better alternative to well-managed VKAs when catheter ablation of AF is planned.…”
Section: Periprocedural Oral Anticoagulationmentioning
confidence: 93%